The Increasing Dine-out Trend: Investigation from Karachiites - Nimra Sharif; Rashid Jamil; Mehreen Nasir (International Journal of Experiential Learning & Case Studies, 2017)
This paper analyzes the increasing preference of people in regard to dining out more in the recent years as compared with eating at home. The trend of dining out is often not to fulfill il hunger instead it is more often because of socializing and just for the sake of trying out new places. The present study further elaborates the impact and consequences of the increased dining out on the changing lifestyle of people. Particularly in Pakistan, the trend of dining out is increasing and is being taken as a leisure trip or a social gathering, which is very different than as it was perceived once when eating out was restricted to occasions and celebrations. This trend is multi-faceted as it is not restricted to a particular segment or class that is being affected by the change in dining out trends. The focus in this study has been on exploring how the trend is increasing amongst the youth as well as a family event, and more importantly, how it is significant despite the increase varies in different social classes. This paper also emphasizes on literature that includes the various strategies used by restaurateurs to encourage increasing dine out behavior. For primary data collection, a questionnaire, containing both open-ended and close-ended questions, was floated and responses of consumers belonging to different areas of Karachi were recorded. The f indings of the study highlighted that male customers are more signif icant contributors to the dine out trend than that of the female customers how it is significant despite the increase varies in different social classes. This paper also emphasizes on literature that includes the various strategies used by restaurateurs to encourage increasing dine out behavior. For primary data collection, a questionnaire, containing both open-ended and close-ended questions, was floated and responses of consumers belonging to different areas of Karachi were recorded. The f indings of the study highlighted that male customers are more signif icant contributors to the dine out trend than that of the female customers how it is significant despite the increase varies in different social classes. This paper also emphasizes on literature that includes the various strategies used by restaurateurs to encourage increasing dine out behavior. For primary data collection, a questionnaire, containing both open-ended and close-ended questions, was floated and responses of consumers belonging to different areas of Karachi were recorded. The f indings of the study highlighted that male customers are more signif icant contributors to the dine out trend than that of the female customers was floated and responses of consumers belonging to different areas of Karachi were recorded. The f indings of the study highlighted that male customers are more signif icant contributors to the dine out trend than that of the female customers was floated and responses of consumers belonging to different areas of Karachi were recorded. The f indings of the study highlighted that male customers are more signif icant contributors to the dine out trend than that of the female customers